Camponeses e Comunistas: Diálogos Possíveis (Ceará, 1947-1953) - Neves, Frederico de Castro (Trabalhos de Antropologia e Etnologia, 2020)
The article seeks to discuss some possibilities of political dialogue between peasants and communists, based on situations that occurred in the 1950s in Brazil, Ceará state. Even with some conceptual and programmatic constraints, some Communist militants act on the basic demands of peasants in the dry semiarid areas that focus on struggles for access to land and water. On the other hand, the article inquires about the possible understandings of the peasants about the convenience of political alliances with communists in specific situations, such as in cases of invasions of cities and pressures for rights to work in public works. Finally, we evaluate the strategic possibilities of this relationship, in terms of a combination of political stances and alternatives of action, which can requalify contemporary peasant struggles.